Zinc Electrode Morphology Evolution in High Energy Density Nickel-Zinc Batteries. (17th March 2016) - Payer, Gizem; Ebil, Özgenç
Abstract : Prismatic Nickel-Zinc (NiZn) batteries with energy densities higher than 100 Wh kg −1 were prepared using Zn electrodes with different initial morphologies. The effect of initial morphology of zinc electrode on battery capacity was investigated. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) reveal that initial morphology of zinc electrode changes drastically after a few charge/discharge cycles regardless of initial ZnO powder used. ZnO electrodes prepared using ZnO powders synthesized from ZnCl2 and Zn(NO3 )2 lead to average battery energy densities ranging between 92 Wh kg −1 and 109 Wh kg −1 while using conventional ZnO powder leads to a higher energy density, 118 Wh kg −1 . Average discharge capacities of zinc electrodes vary between 270 and 345 mA g −1, much lower than reported values for nano ZnO powders in literature. Higher electrode surface area or higher electrode discharge capacity does not necessarily translate to higher battery energy density.